2021
DOI: 10.1530/ec-21-0175
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for IGF-I serum concentration in an adult population: use of the VARIETE cohort for two new immunoassays

Abstract: Context: Measurement of IGF-I is important in the management of patients with growth hormone disorders. Here we aim to establish normative data for two new IGF-I assay kits based on a large random sample of the French general adult population. Subjects and Methods: We measured IGF-I in 911 healthy adults (18–90 years) with two immunoassays (ROCHE Elecsys® and IMMULITE-2000 calibrated against the new IS 02/2547). We compared the data with those of the six immunoassays (iSYS, LIAISON XL, IMMULITE-2000 calibrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Inter-laboratory and inter-assay discrepancies with IGF-I assays are well known [ 6 , 13 , 14 ]; normal reference ranges are specific to each immunoassay, with the greatest differences seen at the highest values [ 6 ] (MQ). Well-validated IGF-I should be calibrated to the current international standard (02/254) [ 15 ].…”
Section: Diagnostic Assessmentmentioning
confidence: 99%
“…Inter-laboratory and inter-assay discrepancies with IGF-I assays are well known [ 6 , 13 , 14 ]; normal reference ranges are specific to each immunoassay, with the greatest differences seen at the highest values [ 6 ] (MQ). Well-validated IGF-I should be calibrated to the current international standard (02/254) [ 15 ].…”
Section: Diagnostic Assessmentmentioning
confidence: 99%
“…The group of Chanson and colleagues 8,9 has produced reference intervals for eight commercially available IGF-1 assay kits in one and the same cohort of healthy control samples. They demonstrated a large variability in the reference ranges of the eight studied IGF-1 assays, despite the fact that all IGF-1 assays were obtained in the same large healthy population and were calibrated against the same recommended standard.…”
Section: Follow-upmentioning
confidence: 99%
“…These variations in assay agreement were independent of the use of mass units or SD scores. Given this variability, if possible, patients with GH disorders should be monitored using the same IGF-I assay at each assessment point (18).…”
Section: Considerations When Using Igf-i As a Biomarkermentioning
confidence: 99%
“…It has been suggested that conversion of IGF-I levels into sds could be used to solve the problem of reference interval variation across assays. However, large variability in the reference ranges of commercially available IGF-I assays, particularly in the upper limits of the reference range, has been found, with only moderate average concordance found across eight immunoassays ( 18 ). These variations in assay agreement were independent of the use of mass units or SDS.…”
Section: Role Of Precision Medicine In Accurate Biochemical Diagnosis...mentioning
confidence: 99%
See 1 more Smart Citation